Totalitarianism: Introduction - Dietrich, Donald J. (Church history, 2001)
Our understanding of the types and meaningful levels of resistance to Hitler's rule has broadened as more complex and reflective studies have unremittingly exposed the political, social, and cultural dynamics supporting the Holocaust and its significance for our culture. Analyses of how and why the Holocaust erupted in Nazi-controlled Europe have elicited studies on the tools and methods of terror in the Third Reich. The works of both Eric Johnson and Robert Gellately, for example, have helped crystallize our understanding of the phenomenon that individual Germans living out their hopes, fears, and, frequently, petty jealousies made operant the ideological and physical terror that empowered the Nazi oppression. The Gestapo and courts, of course, formally carried out the brutalization of society, but they were assisted by countless Germans in fulfilling the Nazi agenda.